A Comparative Study of Lipid Composition of an Undervalued Crustacean (Munida spp.) Captured in Winter and Summer. Issue 9 (21st October 2017) - García-Soto, Bibiana; Trigo, Marcos; Barros-Velázquez, Jorge; Aubourg, Santiago P.
ABSTRACT: This research was focused on the lipid fraction of an undervalued crustacean (lobster krill; Munida spp.) and the comparative study of individuals captured at winter and summer seasons. For this purpose, seasonal variations were analyzed in the muscle (i.e., tail meat) for proximate composition, lipid class distribution, and fatty acid (FA) profile. Mean total lipids ranged from 0.75 ± 0.08% (summer) to 0.92 ± 0.06% (winter), moisture from 77.94 ± 0.25% (winter) to 78.62 ± 0.38% (summer), and protein from 17.93 ± 0.46% (summer) to 18.22 ± 0.46% (winter). Regarding lipid class content (% of total lipids), phospholipids ranged from 64.85 ± 1.29 (summer) to 67.85 ± 2.56 (winter), sterols from 12.15 ± 0.35 (winter) to 13.54 ± 0.54 (summer), triacylglycerols from 0.04 ± 0.02 (summer) to 1.25 ± 0.88 (winter), and free FA from 1.14 ± 0.72 (winter) to 2.19 ± 0.34 (summer). In both seasons, the most abundant FA were C22:6ω3, C16:0, C18:1ω9, and C20:5ω3. Polyunsaturated fatty acids (PUFA) were found to be the most abundant group in samples from both seasons (50.4–55.3%). Higher PUFA values were determined in summer samples, while a highly valuable ω3/ω6 ratio (from 9.11 ± 1.12 in summer to 10.40 ± 1.39 in winter) was observed. It is concluded that in spite of being a low-fat product, the lipid fraction of this underutilized crustacean can provide highly valuable constituents.